Numerical Simulation of Severe Damage to a Historical Masonry Building by Soil Settlement - Atmaca, Esin Erturk; Genc, Ali Fuat; Altunisik, Ahmet Can; Gunaydin, Murat; Sevim, Baris (MDPI, 2023)
Historical masonry structures, which constitute an important part of the historical heritage, exhibit brittle behavior under tensile stresses due to earthquakes or soil movements/settlements. Therefore, they are sensitive to deformation. The soil-structure interaction problems play an important role in the damage to historical masonry structures. Different settlements, slips, and deformations in foundations causes damage to, and/or partial collapse the load-bearing walls. This study provides a numerical simulation of a historic masonry building on the north coast of Turkey, dating from 19th century, which suffered severe damage due to soil settlement by excavation activity near the building. FE models of the building with and without the soil-structure system were created to identify the damage to the building following soil settlement. The height of the soil domain (bounded as a fixed boundary condition) was accepted in the range of 1.5 m to 15 m. The damage propagation between the numerically obtained damage and the existing damage to the building was detailed and compared. In terms of displacement, the maximum vertical and horizontal displacement values reflecting the existing damage to the building were determined as 22 mm and 85 mm, respectively. The soil depth of 6 m was also considered acceptable for deciding the soil-structure interaction. For this, the sum of the rigid basement and the soil depth can be selected to be equal to the total height of the building participating in free vibration. It was concluded that the numerical procedure employed provided an effective representation of existing damage to a building due to soil settlement. Moreover, the procedure described can be adopted for possible collapse simulation.
Keywords: damage propagation; historical masonry building; nonlinear analysis; soil-structure interaction; soil settlement; SEISMIC VULNERABILITY; FAILURE ANALYSIS; EARTHQUAKE; EMPHASIS; TOWERS; MODEL; Construction & Building Technology; Engineering